Influencia de la relación de materia prima / solvente en la extracción de magneso de pilas alcalinas utilizando ácido acético y ácido cítrico. - Medina LLerena, Juana (2014)
It was studied Mn removal from spent batteries alkaline with acetic acid and citric acid as organic acids. Assays were performed in Laboratory of Catalysis, Adsorbents and Materials, Chemical Engineering Faculty. The process extraction was leached with organic acids. It was studied influence of pH, reaction time, ratio influence feedstock / water and organic acid concentration. Mn concentration was read in a spectrophotometer Marca PRIM serie 3522. The results show that pH solution change with degree Mn extraction. It found that is leachable only Mn2+. The higher extraction is reached with 0.5 L of water and it is inflection point. The best conditions for Mn extraction were 25 °C,125 rpm agitation, 15 hours of contact and for CH3COOH 3.15M and 7g/0.5L, but for citric acid for 0.43 M and 3g/0.5L.